DIDACTIC AND METHODOLOGICAL PRINCIPLES OF TRAINING FUTURE TEACHERS FOR THE DEVELOPMENT OF PRIMARY SCHOOL STUDENTS’ UNIVERSAL LEARNING SKILLS - Oliiar, Mariia; Fomin, Kateryna (Mountain School of Ukrainian Carpaty, 2022)
The study deals with the issue of didactic-methodological fundamentals of the development of future primary school teachers’ professional competencies regarding the improvement of primary school students’ universal learning skills according to the requirements of the State Standard through a scientific understanding of approaches to this problem in Pedagogy, Psychology, and particular methods. It is noted that the foundation of schoolchildren’s cognitive activity and successful learning activity begins in primary school. The educational activity is considered the leading type of primary school students’ activity, combining conceptual structures (learning task, educational action, control, and assessment action). The authors of the research emphasize that early school age is sensitive to cognitive activity; therefore the primary school teacher’s most important task is the development of a set of cognitive universal learning skills that will effectively ensure the development of the capability of successfully obtaining new knowledge and competences, that is, the ability to learn. We provided a list of basic universal skills for primary school students to master. The authors consider educational games, communication, and project activities ways of developing students’ universal learning skills. It is noted that universal learning skills become the basis for the formation of cognitive activity and independence of primary schoolchildren, their educational and cognitive competence, which are the most important attributes of personally oriented learning at all levels of education. The authors of the article learned that the problem of the formation and development of primary schoolchildren’s universal learning skills is quite complicated and causes great difficulties even for experienced teachers. The source for such a conclusion was the analysis and processing of the results of the questionnaire conducted among students and in-service teachers. The contradiction between the importance of the development of primary school students’ universal learning skills when studying various disciplines and teachers’ insufficient methodical and organizational-pedagogical readiness was revealed. Future teachers’ readiness to facilitate primary schoolchildren’s educational processes is determined by cognitive and activity criteria. The content of the didactic and methodological training of future teachers for the formation of primary school students’ universal learning skills is analyzed. In our opinion, this content consists of tasks for seminars and practical classes, solving situational problems, individual tasks, case methods, organization of students’ independent work, creation of exercises and tasks for primary school students, and their assessment during pedagogical practice, etc.